Microwave-Heating-Assisted Synthesis of Ultrathin and Ultralong Hydroxyapatite Nanowires Using Biogenic Creatine Phosphate and Their Derived Flexible Bio-Paper with Drug Delivery Function - Yu Zhang; Ying-Jie Zhu; Si-Yi Li; Li-Ying Dong; Han-Ping Yu (Molecules)
With an ultrahigh aspect ratio and a similar chemical composition to the biomineral in bone and tooth, ultralong hydroxyapatite nanowires (UHAPNWs) exhibit a meritorious combination of high flexibility, excellent mechanical performance, high biocompatibility, and bioactivity. Despite these exciting merits, the rapid and green synthesis of UHAPNWs remains challenging. In this work, we have developed an environment-friendly, rapid, and highly efficient synthesis of ultrathin UHAPNWs by the microwave-assisted calcium oleate precursor hydrothermal method using biogenic creatine phosphate as the bio-phosphorus source. Owing to the controllable hydrolysis of bio-phosphorus-containing creatine phosphate and the highly efficient heating of microwave irradiation, ultrathin UHAPNWs with a homogeneous morphology of several nanometers in diameter (single nanowire), several hundred micrometers in length, and ultrahigh aspect ratios (>10,000) can be rapidly synthesized within 60 min. This effectively shortens the synthesis time by about two orders of magnitude compared with the traditional hydrothermal method. Furthermore, ultrathin UHAPNWs are decorated in situ with bioactive creatine and self-assembled into nanowire bundles along their longitudinal direction at the nanoscale. In addition, ultrathin UHAPNWs exhibit a relatively high specific surface area of 84.30 m2 g–1 and high ibuprofen drug loading capacity. The flexible bio-paper constructed from interwoven ibuprofen-loaded ultrathin UHAPNWs can sustainably deliver ibuprofen in phosphate-buffered saline, which is promising for various biomedical applications such as tissue regeneration with anti-inflammatory and analgesic functions.